Pertanggungjawaban Hukum Terhadap Korban Atas Biaya Restitusi yang Tidak Terpenuhi Pada Putusan Pengadilan Negeri Tangerang Nomor 1712/Pid.Sus/2021/Pn.Tng - Firmansyah, Hery; Sun Lisyah, Lisyah (UNES Law Review, 2023)
Restitution is compensation given to victims of criminal acts who have suffered both materially and physically, mentally or emotionally as a result of the perpetrator of the crime. The right to restitution is regulated in Government Regulation No. 3 of 2002. This right can be in the form of return of property, payment of compensation for loss or suffering, or reimbursement of costs for certain actions. Generally, the right to restitution is given to victims of serious crimes. However, not all victims receive this right fully, as happened in case No. 1712/PID.SUS/2021/PN.TNG, where the child victim was sexually assaulted, causing the victim to become pregnant and give birth to a child. This research was conducted using normative research methods with a statutory and case approach. This research data is of secondary type with primary and secondary legal materials which will be analyzed qualitatively. The research results show that the convicted person who is unable to fulfill the restitution demands will be subject to substitute imprisonment that does not exceed the threat of the main punishment and the state compensates a certain amount of restitution to victims of sexual violence according to the court's decision through the victim assistance fund.